2010
DOI: 10.1208/s12248-010-9246-5
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Modulation of Aracytidine (Ara-C) Effects by GTI-2040, a Ribonucleotide Reductase Inhibitor, in K562 Human Leukemia Cells

Abstract: Abstract. GTI-2040 is a potent antisense to the M2 subunit of the ribonucleotide reductase (RNR), an enzyme involved in the de novo synthesis of nucleoside triphosphates. We hypothesized that combination of GTI-2040 with the cytarabine (Ara-C) could result in an enhanced cytotoxic effect with perturbed intracellular deoxynucleotide/nucleotide (dNTP/NTP) pools including Ara-C triphosphate (Ara-CTP). This study aims to provide a direct experimental support of this hypothesis by monitoring the biochemical modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…C/EBPα, CCAAT/enhancer binding protein α; FLT3, FMS-like tyrosine kinase-3; HK3, hexokinase 3; KLF5, krüppel-like factor 5. Ara-C treatment, various novel drug combinations have been explored (70,71). Recently, it was demonstrated that miR-181a could sensitize a chemotherapy-resistant HL60 cell line to Ara-C treatment (72).…”
Section: Regulators Targeting C/ebpα In Myeloid Differentiation and Lmentioning
confidence: 99%
“…C/EBPα, CCAAT/enhancer binding protein α; FLT3, FMS-like tyrosine kinase-3; HK3, hexokinase 3; KLF5, krüppel-like factor 5. Ara-C treatment, various novel drug combinations have been explored (70,71). Recently, it was demonstrated that miR-181a could sensitize a chemotherapy-resistant HL60 cell line to Ara-C treatment (72).…”
Section: Regulators Targeting C/ebpα In Myeloid Differentiation and Lmentioning
confidence: 99%
“…41,42 To improve the cytotoxic activity of Ara-C treatment, various novel drug combinations have been explored. 43,44 Recently, it was demonstrated that miR-181a can sensitize a chemotherapyresistant HL60 cell line to Ara-C treatment. 29 Having found that miR-181a is up-regulated in response to lenalidomide, we asked whether pretreatment of AML cells with this compound can similarly sensitize the cells to Ara-C.…”
mentioning
confidence: 99%
“…23 In this study, aCD33LN/GTI-2040 and Ara-C were evaluated as a combination in Kasumi-1 and K562 cells. IC 50 values were determined by MTS assay.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have indicated a therapeutic benefit of combining GTI-2040 with Ara-C in the treatment of AML. 23 In this study, aCD33LN/GTI-2040 and Ara-C were evaluated as a combination in Kasumi-1 and K562 cells. IC 50 values were determined by MTS assay.…”
Section: Cd33 Expression and Acd33lnmentioning
confidence: 99%